ROLLER GRATE WITH INCREASING COVERAGE GROUND SURVEY WORK CORNER (Conferencea, 2022)
Ground with several types of building materials are used in production of the roller. Depending on the degree of crushing of materials, the output device in the hole: a) large b-crushing Secondary crushing v)finely crushing. Depending on the expenses to the advantage of: a) Stasionar b) xarakatlanuvchi. Grate depending on the number of the working rollers: a)with a roller b)a roller with two c)three rollers g) with four roller [1-8].